Acetylcholinesterase inhibitors (nerve agents) as weapons of mass destruction: History, mechanisms of action, and medical countermeasures. (15th December 2020) - Aroniadou-Anderjaska, Vassiliki; Apland, James P.; Figueiredo, Taiza H.; De Araujo Furtado, Marcio; Braga, Maria F.
Abstract: Nerve agents are organophosphorus acetylcholinesterase inhibitors. Acute exposure to nerve agents can cause rapid death. In this review, we summarize the history of nerve agent development and use in warfare, the mechanisms by which these agents cause death or long-term brain damage, and the treatments for preventing death or long-term morbidity. The G-series nerve agents, tabun, sarin, soman, ethyl sarin, and cyclosarin, were developed by the Nazis. VX, the best-known of the V-series agents, was synthesized in the 1950's by a British scientist. Little is known about the development of the novichoks (the "A-series") by the former Soviet Union. Nerve agents were used for the first time in the battlefield by the Iraqi government in the Iran–Iraq War, in the 1980s. The Chemical Weapons Convention, in 1993, banned all chemical weapons production and use, yet, sarin was subsequently used in terrorist attacks in Japan and, recently, in the war in Syria. Pyridostigmine has been used as a prophylactic treatment, and bioscavengers are presently investigated as a better alternative. Atropine, along with an oxime, can prevent rapid death from the nerve agent-induced peripheral cholinergic crisis. Treatment with diazepam or midazolam for the cessation of nerve agent-induced status epilepticus cannot protect against brain damage, and, therefore, these benzodiazepines should be replaced by novel anticonvulsants and neuroprotectants. The AMPA/GluK1 receptor antagonist LY293558 (tezampanel) has shown superior antiseizure and neuroprotective efficacy against soman, particularly when administered in combination with caramiphen, an antagonist of muscarinic and NMDA receptors. This article is part of the special issue entitled 'Acetylcholinesterase Inhibitors: From Bench to Bedside to Battlefield'. Highlights: Nerve agents were first developed by the Nazis. Still used in wars and terrorist attacks, nerve agents continue to be a major threat. Peripheral cholinergic crisis and status epilepticus can cause death upon exposure. Prophylactic treatments and better oximes are under intense investigation. Certain novel treatments are more effective against brain damage than benzodiazepines.